The Role of the Environment in Human Life in the Novels Tambora 1815 and Medulla Sinculasis by Paox Iben Mudhaffar - Hendri; Wahidatul Murtafi’ah (Jurnal Disastri (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2024)
The purpose of this research is to describe (1) the form of environmental role in human life, (2) the form of human attitude to the environment, (3) the form of local wisdom in its relation with environment in novel Medulla Sinculasis and Tambora 1815 by Paox Iben Mudhaffar. This research was qualitative descriptive. The source of data  was the novels Medulla Sinculasis and Tambora 1915 by Paox Iben Mudhaffar. The collection of the data used document content analysis (read-note-analysis). Analysis of the data in this study is a qualitative descriptive analysis technique is done by categorizing, describing, and conclusion.  In this research, the researchers chose the novels Medulla Sinculasis and Tambora 1815 as data sources considering that these novels were the most appropriate to study among Paox Iben's other works. The Tambora 1815 novel used is the first printed novel, March 2015 published by Bukudaku Addressra Publishing, Mataram with a book thickness of 301 pages, ISBN: 978-979-18863-1-4 and the Medulla Sinculasis novel used is the first printed novel, January 2011 published by IruS (Rumah Arus Institute) Mataram, Lombok with a book thickness of 324 pages, ISBN: 979-1698-045-94-7. The results of this research are as follows. First, the role of environment represented in the novels Medulla Sinculasis and Tambora 1815  consists of : (a) the environment as the source of food, (b) the environment as the source of medicines, (c) the environment as the source of building material, (d) the environment as living place, (e) the environment as the provider of payment tool (barter), (f) the environment as a means of livelihood, (g) the environment as the source of water, (h) the  environment as the provider of things for means of transportation, and (i) the environment as tourist object.